Citizen science or scientific citizenship? Disentangling the uses of public engagement rhetoric in national research initiatives. Issue 1 (December 2016) - Woolley, J.; McGowan, Michelle; Teare, Harriet; Coathup, Victoria; Fishman, Jennifer; Settersten, Richard; Sterckx, Sigrid; Kaye, Jane; Juengst, Eric
Abstract Background The language of "participant-driven research, " "crowdsourcing" and "citizen science" is increasingly being used to encourage the public to become involved in research ventures as both subjects and scientists. Originally, these labels were invoked by volunteer research efforts propelled by amateurs outside of traditional research institutions and aimed at appealing to those looking for more "democratic, " "patient-centric, " or "lay" alternatives to the professional science establishment. As mainstream translational biomedical research requires increasingly larger participant pools, however, corporate, academic and governmental research programs are embracing this populist rhetoric to encourage wider public participation. Discussion We examine the ethical and social implications of this recruitment strategy. We begin by surveying examples of "citizen science" outside of biomedicine, as paradigmatic of the aspirations this democratizing rhetoric was originally meant to embody. Next, we discuss the ways these aspirations become articulated in the biomedical context, with a view to drawing out the multiple and potentially conflicting meanings of "public engagement" when citizens are also the subjects of the science. We then illustrate two uses of public engagement rhetoric to gain public support for national biomedical research efforts: its post-hoc use in the "care.data" project of the National Health Service in England, and its proactive uses in the "Precision Medicine Initiative" of the United States White House. These examples will serve as the basis for a normative analysis, discussing the potential ethical and social ramifications of this rhetoric. Summary We pay particular attention to the implications of government strategies that cultivate the idea that members of the public have a civic duty to participate in government-sponsored research initiatives. We argue that such initiatives should draw from policy frameworks that support normative analysis of the role of citizenry. And, we conclude it is imperative to make visible and clear the full spectrum of meanings of "citizen science, " the contexts in which it is used, and its demands with respect to participation, engagement, and governance.